1985
DOI: 10.1159/000183398
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Oxalate Restriction in Association with Calcium Restriction to Decrease the Probability of Being a Stone Former: Insufficient Effect in Idiopathic Hypercalciuria

Abstract: The probability of being a stone former (PSF) was calculated in 3 groups of idiopathic calcium stone formers [with normocalciuria (NC), dietary hypercalciuria (DH) and idiopathic hypercalciuria (IH)] in 4 conditions: while (1) on a free diet; (2) on a calcium- and oxalate-restricted diet during 4 days; (3) after an oxalate load, while on a 1.5-gram calcium diet, and (4) after an oxalate load while on a calcium-restricted diet. Combined calcium and oxalate restriction significantly decreased PSF only in NC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Intake of a moderately high-calcium diet appears to be beneficial to decrease the urinary oxalate excretion and IGFBP-7 in patients with idiopathic hypercalciuria (Nakada et al, 1988). Increase of IGFBP-7 with the oxalate load was significantly greater on calcium-restricted than on calcium-unrestricted diets in all groups of patients (Bataille et al, 1983). We found that IGFBP-7 mRNA expression was higher in LL chickens than in AA chickens, and a strain difference was observed in IGFBP-7 expression between LA and LL chickens (Table 6).…”
Section: Expression Of Igfbp-2 Igfbp-5 Igfbp-7 and Igfbp-3 Genes Imentioning
confidence: 82%
“…Intake of a moderately high-calcium diet appears to be beneficial to decrease the urinary oxalate excretion and IGFBP-7 in patients with idiopathic hypercalciuria (Nakada et al, 1988). Increase of IGFBP-7 with the oxalate load was significantly greater on calcium-restricted than on calcium-unrestricted diets in all groups of patients (Bataille et al, 1983). We found that IGFBP-7 mRNA expression was higher in LL chickens than in AA chickens, and a strain difference was observed in IGFBP-7 expression between LA and LL chickens (Table 6).…”
Section: Expression Of Igfbp-2 Igfbp-5 Igfbp-7 and Igfbp-3 Genes Imentioning
confidence: 82%